New applications for importance-performance analysis (IPA) in higher education: Understanding student satisfaction - Fraser, McLeay; Andrew, Robson; Mazirah, Yusoff* (Emerald Publishing Limited, 2017)
Purpose The constantly evolving higher education (HE) sector is creating a need for new business models and tools for evaluating performance. In this paper, an overview of the importance-performance analysis (IPA) model and its applicability as a management tool for assessing student satisfaction in the HE sector is provided. The purpose of this paper is to apply IPA in a new and novel manner, undertaking analysis at three levels; the individual student, for individual attributes and at a construct or factor level which combines individual attributes that are correlated. A practical application is illustrated, assessing the gap between the importance placed on specific student satisfaction attributes and corresponding levels of student-perceived performance realised.